Applicability of the Proposed Japanese Model for the Classification of Gastric Cancer Location: The "PROTRADIST" Retrospective Study. (4th May 2017) - Marano, Luigi; Petrillo, Marianna; Pezzella, Modestino; Patriti, Alberto; Braccio, Bartolomeo; Esposito, Giuseppe; Grassia, Michele; Romano, Angela; Torelli, Francesco; De Luca, Raffaele; Fabozzi, Alessio; Falco, Giuseppe; et al.
ABSTRACT: Background : The extension of lymphadenectomy for surgical treatment of gastric cancer remains discordant among European and Japanese surgeons. Kinami et al. (Kinami S, Fujimura T, Ojima E, et al. PTD classification: proposal for a new classification of gastric cancer location based on physiological lymphatic flow. Int. J. Clin. Oncol. 2008;13:320–329) proposed a new experimental classification, the "Proximal zone, Transitional zone, Distal zone" (PTD) classification, based on the physiological lymphatic flow of gastric cancer site. The aim of the present retrospective study is to assess the applicability of PTD Japanese model in gastric cancer patients of our Western surgical department. Methods : Two groups of patients with histologically documented adenocarcinoma of the stomach were retrospectively obtained: In the first group were categorized 89 patients with T1a–T1b tumor invasion; and in the second group were 157 patients with T2–T3 category. The data collected were then categorized according to the PTD classification. Results : In the T1a–T1b group there were no lymph node metastases within the r -GA or r -GEA compartments for tumors located in the P portion, and similarly there were no lymphatic metastases within the l -GEA or p -GA compartments for tumors located in the D portion. On the contrary, in the T2–T3 group the lymph node metastases presented a diffused spreading with no statistical significance between the two classification models. Conclusions : Our results show that the PTD classification based on physiological lymphatic flow of the gastric cancer site is a more physiological and clinical version than the Upper, Medium And Lower classification. It represents a valuable and applicable model of cancer location that could be a guide to a tailored surgical approach in Italian patients with neoplasm confined to submucosa. Nevertheless, in order to confirm our findings, larger and prospective studies are needed.